(untitled) (Palimpsesto, 2023)
The next research came from the question about the images of the disappeared detainees in Chile and the relationship that their family and friends have with its. As theoretical support, we follow the philosophy of the image Bildwissenschaft, initiated in the 1990s, specifically we use the triad proposed by Hans Belting, "image-medium-body" to understand the agency of images. Regarding the methodology, we resorted to ethnography, investigating the image experience, practices, and relationships that family and friends maintain with their absentees. In this sense, it is not a property philosophical work, although its basis is. On this basis, the research allows us to conclude that the relationships with the image depend on the closed is the kinship, on the ways of coping with grief, but above all, on the particularities of the person. In turn, we observe that the experiences of family and friends are formulated not only in affective terms, but also in political terms. Finally, understanding that the Bildwissenschaft was born in the European field, the research contributes formulations typical of Latin America, because it shows that the cases of Chilean forced disappearance exceed in many ways the practices observed in other contexts.